KERATOSIS OBTURANS - Jerry Tobing (Universitas Methodist Indonesia, 2018)
Keratosis obturans is a disease of the outer ear canal that is rarely found, both because of rare cases and misdiagnosis. Writing refarat will discuss more deeply from the understanding to the management of this disease which aims to prevent the diagnosis of this disease in the future by the treating doctor. Management in this case is carried out by an ENT-KL specialist, but to diagnose and support the general practitioner, it is important to know and do it. Also included is to be able to distinguish this disease from other types of diseases in the ear canal. Keratosis obturans is often associated with sinusitis and bronchhiectasis and is also often equated with cholesteatoma in the ear canal. Diagnosis requires CT scanning of the temporal bone, histopathological examination of each granulation tissue and audiogram to see conductive type hearing loss.